HABITUS DIGITAL GENERASI MUSLIM MILINEAL DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Tamsil; Jawahir, Achmad; Aldi Ubaidillah, Muh.; Musdalipah; Setiawan, Aan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The rapid development of digital tecnologi has shaped the digital habitus of the Muslim millinneal generation, influencing the way they think, interact, learn, dan practice their religion. At the some time, Islamic education is required to adapt to these changes without neglecting Islamic value. Agains this background, this study addresses the following rearch question: (1) how is the digital habitus of the Muslim millinneal generation farmed in the are of digital transformation? (2) what are the inplications of the digital habitus of the Muslim millinneal generation for Islamic education in terms of its opportunities and challenges? and (3) what transformation strategi are needed to realize an Islamic digital habitus in Islamic education?. This study aims to analyze the formation of digital habitus, examine its implications for Islamic eduqation, and formulate the concept of an Islamic digital habitus. A qualitative approarch was emplayed using the library research method. Data were collected for books, jurnal articles, and other relevant scholarly documents and analyzed using descriptive analysis. The findings indicate that the digital habitus of the Muslim millinneal generation has two major implications. First, it creates significant opportunities for strengthening Islamic literacy, technology based learning, digital da’wah, collaborative learning, and expanding access to learning resources.second, it presents challenges, including the spread of misinformation, the degradation of digital ethics, inappropriate online content, and religion information with unclear sources and questionable credibility, therefore, the transformation of Islamic eduqation toward an Islamic digital baitus requires strategies such as strengthening Islamic digital literacy, developing an integrative curriculum, reinforcing the role of eduqations, and promoting critical digital learning media grounded in the values of tawhid, sharia, ethics, and responsibility. This study propses the concept of an Islamic digital habitus as a new paradigm for developing Islamic eduqation that is adaptive to digital transformation while preserving the fundamental value of Islam